Plight of left-handed dentists in clinical dentistry - Samuel, Selwin Gabriel; Anandan, Sujatha (Journal of Oral Research, 2019)
A dentist can either be right-handed or left handed. A right-handed dentist cannot work on a left-sided chair and vice versa.1 Though it is not impossible to work in a chair not suited to the handedness of the dentist, the working efficiency is drastically reduced, thereby compromising the outcome of the treatment. Every dental student discovers this problem only when he/she faces patients. Most of the dental colleges do not have left-sided chairs in all departments, while some dental colleges are devoid of left-sided chairs as there are very few left-handed individuals and a very small fraction of left-handers opt for a career in dentistry. This leaves left-handed students with no other option but using the right-handed chairs,2 leading to musculoskeletal disorders.3 When left-sided chairs are available, the problem arises when the chair is under repair or if any vital component of the chair fails to function. The student will be asked to switch to a right-sided chair which again becomes problematic. The problems do not end with college. A left-handed dentist would certainly install a left-sided chairs in private practice, but this impedes the clinician from then obtaining the help of a consultant who is not necessarily left-handed.